ROLE OF PAPANICOLAOU SMEAR IN MAPPING OUT CERVICAL EPITHELIAL MORPHOLOGY IN WOMEN WITH INFERTILITY: MODIFIED BETHESDA CLASSIFICATION - Javed, Sumaira; Huma, Zilli; Sadaf, Aisha; Hameed, Nadira; Sherin, Fatima; Momin, Nabila (Journal of Ayub Medical College Abbottabad, 2019)
Background: Papinocolaou smear (PAP) smear has a specificity of 98% in detecting early changes in cervical epithelium in women above 21 years, thus its avocation as a screening tool for cervical cancers worldwide. In Pakistan with a lack of awareness in our population as well as socioeconomic conditions there is no such screening program. Infertility on the other hand affects 22% of women in Pakistan and thus one of the most common cause of physician visits. Both cervical cancers and infertility have sexually transmitted diseases (STD's) as common causes with studies reporting ~75% of women have an STD at-least once during their life, presenting with cervical epithelial cell lesions. Thus, the present study was carried out to identify patterns of cervical cell morphology in women with infertility using PAP smear. Methods: Cervical smears were taken from infertile women and fertile women (n=150), stained with H&E and PAP stains, and graded according to Bethesda Classification 2001. Analysis of data was done by using SPSS version 20 and MS Excel. Results: The mean age of participants was ~29 years. Epithelial cell morphology of these smears showed significant difference among three groups (p value 0.037) with severity in infertile women. Further in the subgroup of secondary infertile women, there were more abnormal smears as compared to primary as well as a higher grade of severity by Pap smear. Conclusion: Thus, it is concluded that women presenting with some level of infertility are at a higher risk of having cervical epithelial abnormalities. Keywords: PAP smear; Infertility; Epithelial lesions